2013
DOI: 10.1021/es304299v
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Inorganic Arsenic Species in Rice after Nitric Acid Extraction by HPLC-ICPMS: Verification Using XANES

Abstract: The measurement of As species in rice is normally accomplished by extraction followed by HPLC-ICPMS analysis. This method, however, has not been comprehensively validated by comparing these speciation results with XANES, which does not require sample extraction, due to the challenge of conducting XANES analysis at very low As concentrations. In this study As speciation data using nitric acid extraction/HPLC-ICPMS and XANES are compared to verify the efficacy of using 2% v/v nitric acid extraction and HPLC-ICPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 44 publications
3
64
1
Order By: Relevance
“…19,No. 3 analysis and in situ bulk XANES [67] (Figure 3A). The samples had low As concentrations ranging from 0.20 to 0.34 mg/g.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…19,No. 3 analysis and in situ bulk XANES [67] (Figure 3A). The samples had low As concentrations ranging from 0.20 to 0.34 mg/g.…”
Section: Reviewmentioning
confidence: 99%
“…This study provided evidence of good agreement between the two techniques and demonstrated the high sensitivity of XANES offered by modern synchrotron beamlines. In rice grains, As is present as As(III), As(III)-thiol complexes, As(V), and DMA [43,67].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common use of XAS for As speciation is the analysis of X-ray absorption near-edge structure (XANES), which reveals the most probable chemical environment around As by matching the spectral characteristics, including whiteline energy, to the standard compounds. This method has provided good results for the speciation of As compounds in rice (Maher et al, 2013). Studies comparing both methods demonstrate that compounds such as As III -S have not been found by the traditional method, but have been found by XAS; this has been attributed to its oxidation during extraction with nitric acid.…”
Section: Current Legislation For Arsenic Level In Rice Grainmentioning
confidence: 99%
“…The iAs content varied with the region of Italy the samples came from. Maher et al 188 extract arsenic species using 2% HNO 3 before measurement by the coupled technique. Both cation and anion exchange columns are used for separation.…”
mentioning
confidence: 99%